Recent Patents on Preparation Methods and Mechanical Stability of Superhydrophobic Surface - Li, Zhaolong; Liu, Yingtao (Recent Patents on Engineering, 2022)
Background: Superhydrophobic surfaces have unique wettability and have shown broad application prospects in many fields, such as self-cleaning and lubrication drag reduction. However, the superhydrophobic surfaces are severely restricted by their poor mechanical stability in practical application, and the mechanical stability of the superhydrophobic surface is always affected by different preparation methods. Therefore, people pay more attention to the preparation methods of superhydrophobic surfaces. Objective: The study aims to improve the mechanical stability of the superhydrophobic surface and expand the application fields of the superhydrophobic surfaces; preparation methods of the superhydrophobic surface have been continuously improved. Methods: This paper reviews various representative patents and papers on preparation methods of the superhydrophobic surface at home and abroad. Results: In this review, the basic methods of preparing superhydrophobic surfaces were introduced, and three typical methods were summarized, such as etching method, coating method, and sol-gel method, then their advantages and disadvantages were discussed. In combination with the latest research progress, it is proposed that the use of environmentally friendly low surface energy modifiers and the use of the one-step method to prepare superhydrophobic surfaces are the future development trends. Aiming at the problem of the mechanical stability of superhydrophobic surfaces, the instability mechanism and stability evaluation methods of superhydrophobic surfaces under mechanical action are reviewed, and three basic methods to improve the mechanical stability of superhydrophobic surfaces are proposed. Conclusion: The optimization of the preparation method of the superhydrophobic surface is beneficial to improve the mechanical stability of the superhydrophobic surface and expand the application prospect of the superhydrophobic surfaces in various fields. More patents and papers on the superhydrophobic surface will be invented later.
Keywords: micro-nano rough structure